2015
DOI: 10.1002/ejic.201500654
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Involving Hydrogen Sulfite Ions, Chlorite Ions, and Hypochlorous Acid as Key Intermediates of the Autocatalytic Chlorine Dioxide–Thiourea Dioxide Reaction

Abstract: The kinetics of the chlorine dioxide–thiourea dioxide reaction was investigated by monitoring absorbance–time profiles at λ = 360 nm. Under acidic conditions, the primary carbon‐containing product is cyanamide, not urea as considered previously for many oxidation reactions of thiourea dioxide. Increase of the rate of the reaction by an increase of pH can be readily explained by the slow pH‐dependent formation of a more reactive form of thiourea dioxide (TDO) that is produced steadily and unavoidably as the sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 47 publications
1
13
2
Order By: Relevance
“…We therefore concluded that it is important to use a TDO stock solution at the same age to establish a reliable kinetic model. Thus, except otherwise stated, all of the experimental runs were initiated having the age of the TDO solution to be 270 ± 4 s. At the same time, this series of kinetic runs appears to suggest that the aged form of TDO is significantly more reactive than the fresh one, which is quite consistent with what was observed in the case of other redox reactions of TDO. …”
Section: Resultssupporting
confidence: 67%
“…We therefore concluded that it is important to use a TDO stock solution at the same age to establish a reliable kinetic model. Thus, except otherwise stated, all of the experimental runs were initiated having the age of the TDO solution to be 270 ± 4 s. At the same time, this series of kinetic runs appears to suggest that the aged form of TDO is significantly more reactive than the fresh one, which is quite consistent with what was observed in the case of other redox reactions of TDO. …”
Section: Resultssupporting
confidence: 67%
“…The absorbance‐time curves showed a sigmoidal profile (Figure ) and the rate‐time curves a bell‐shaped one (Figure ). Although these features are also compatible with autocatalysis, this kind of process is to be expected for reactions involving considerably reactive products or intermediates rather than for the ligand replacement reactions from the notably inert Cr(III) complexes. Thus, the long‐lived intermediate‐based explanation should be considered more probable in the present case.…”
Section: Resultsmentioning
confidence: 96%
“…Quite recently, in a number of subsequent papers, it has also been demonstrated experimentally that TDO, even under acidic aqueous conditions, ages, and several times, the aged form of TDO is more reactive toward the corresponding oxidizing agents ,, than its original form. The only exception was found to be the TDO–bromate reaction, where no effect of aging was found when the TDO solution was not older than a day.…”
Section: Resultsmentioning
confidence: 99%
“…It is demonstrated that the title system may be classified as an autocatalysis-driven clock reaction because the clock species iodine may as well appear, although just transiently, in substrate excess after a well-defined and reproducible time lag. It is also highlighted that the Landolt time depends on the age of the stock TDO solution in the case of the TDO–periodate reaction likewise in the TDO–iodine, TDO–chlorine dixoide, , and TDO–iodate reactions. As was shown, the kinetic model of the overall system was gradually built up from those of its subsystems as in the TDO–iodine and the TDO–iodate reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation